Influence for nonprofit leaders - Friedman, Deborah (Ideas into action guidebooks., 2013)
Influence is an essential component of leadership, especially in a nonprofit environment. Since relationships are vital for a nonprofit's success, a leader needs to be able to influence employees, volunteers, and stakeholders in order to meet the challenges ahead. It can be especially difficult when you have to influence those who are neutral or even opposed to your ideas. This book will help you to cultivate and use your influence to achieve the results your nonprofit needs.